2020
DOI: 10.1111/boc.201900055
|View full text |Cite
|
Sign up to set email alerts
|

Increased intracellular survival of Salmonella Typhimurium ST313 in HIV‐1‐infected primary human macrophages is not associated with Salmonella hijacking the HIV compartment

Abstract: Background Non‐typhoidal Salmonella (NTS) causes a severe invasive syndrome (iNTS disease) described in HIV‐positive adults. The impact of HIV‐1 on Salmonella pathogenesis and the molecular basis for the differences between these bacteria and classical diarrhoeal S. Typhimurium remains unclear. Results Here, we show that iNTS‐associated S. Typhimurium Sequence Type 313 (ST313) bacteria show greater intracellular survival in primary human macrophages, compared with a ‘classical’ diarrhoeal S. Typhimurium ST19 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Typhimurium ST313 demonstrated a correlation between lower FliC expression, reduced inflammatory responses, and enhanced survival in macrophages; these phenotypes were linked to the high invasiveness and bacteremia associated with clinical S . Typhimurium ST313 infections 56 58 . One caveat of these studies, however, was that conclusions were drawn from the comparison of in vitro cellular responses between ST313 and ST19 isolates, two distinct lineages of NTS.…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium ST313 demonstrated a correlation between lower FliC expression, reduced inflammatory responses, and enhanced survival in macrophages; these phenotypes were linked to the high invasiveness and bacteremia associated with clinical S . Typhimurium ST313 infections 56 58 . One caveat of these studies, however, was that conclusions were drawn from the comparison of in vitro cellular responses between ST313 and ST19 isolates, two distinct lineages of NTS.…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte-derived macrophages (hMDMs) were differentiated from PBMCs according to the method described in Lê-Bury et al. ( 39 ) for six days. CD3 + cells and naïve B cells were isolated from donor PBMCs using the magnetic bead Pan T isolation kit and B Cell Isolation Kit II from Miltenyi respectively, according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) were obtained by cytapheresis from healthy donors from the French Blood bank (Etablissement Francais du sang, EFS) and isolated using a Ficoll density gradient. Monocyte-derived macrophages (hMDMs) were differentiated from PBMCs according to the method described in Le-Bury et al (39) for six days. CD3 + cells and naïve B cells were isolated from donor PBMCs using the magnetic bead Pan T isolation kit and B Cell Isolation Kit II from Miltenyi respectively, according to the manufacturer's instructions.…”
Section: Cellsmentioning
confidence: 99%
“…The severity of iNTS in PLWH may be due to an impaired immune response to the infection, as suggested in a study by MacLennan et al [ 84 ]; specifically, it was reported that an excess of antibodies against Salmonella lipopolysaccharide (LPS) is associated with a reduction in Salmonella killing. Other reasons behind the severity of iNTS in PLWH may be found in the dysregulation of proinflammatory cytokine release, such as TNF alpha, IL-10 and IL-12 [ 85 ], the attenuation of transcription factor nuclear κB (NFκB)-mediated inflammation [ 86 ], the defective activity of monocytes phagocytosis [ 87 ] and the apparent enhanced capacity of a specific sequence type 313 (ST313) of S. typhimurium of surviving in HIV-infected macrophages and their defective phagocytic ability [ 88 , 89 ].…”
Section: Salmonellosismentioning
confidence: 99%